2012
DOI: 10.1115/1.4006323
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Network Classifiers for Set-Based Collaborative Design

Abstract: Complex engineering design problems are often decomposed into a set of interdependent, distributed subproblems that are solved by domain-specific experts. These experts must resolve couplings between the subproblems and negotiate satisfactory, system-wide solutions. Set-based approaches help resolve these couplings by systematically mapping satisfactory regions of the design space for each subproblem and then intersecting those maps to identify mutually satisfactory system-wide solutions. In this paper, Bayesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 35 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…As the number of design points to be evaluated has a direct influence on the accuracy of feasible solution spaces, designers may face difficulty in choosing an appropriate sample size to ensure reasonable accuracy. The results reported by Shahan et al [2] also indicate the dependency of the number of initial training sample points on the shape of a feasible region boundary obtained from Bayesian network classifiers. Furthermore, it is often observed that the identified feasible regions represent a small portion of the initial design space and a large number of sample points are expended in evaluating unsatisfactory design points.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As the number of design points to be evaluated has a direct influence on the accuracy of feasible solution spaces, designers may face difficulty in choosing an appropriate sample size to ensure reasonable accuracy. The results reported by Shahan et al [2] also indicate the dependency of the number of initial training sample points on the shape of a feasible region boundary obtained from Bayesian network classifiers. Furthermore, it is often observed that the identified feasible regions represent a small portion of the initial design space and a large number of sample points are expended in evaluating unsatisfactory design points.…”
Section: Introductionmentioning
confidence: 83%
“…The detailed In response to these issues, set-based design approaches have become more promising as they tend to attain design requirements by exploring a set of satisfactory design solutions. Shahan et al [2] proposed a set-based collaborative design method that classifies the design space into satisfactory and unsatisfactory regions by employing Bayesian network classifiers. This method is further applied in the hierarchical design of negative stiffness meta-materials at micro-, meso-, and macro-scales [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…3.3 Gaussian Naive Bayes. Bayesian classifiers, which are based on Bayes' theorem, have been found to perform well on a variety of classification problems [3,31,32]. The NB classifier is a well-known representative of the Bayesian classifiers.…”
Section: Description Of Classification Techniquesmentioning
confidence: 99%
“…One example is the set-based design, which focuses on solving distributed design problems by delaying commitment to a single point solution and preserving a diversity of options for identifying mutually satisfactory cross-disciplinary solutions [2]. In this context, classifiers have been used to solve distributed, multidisciplinary design problems, which are decomposed into interdependent subproblems that share coupled design variables [3]. A similar set-based approach may be applied to a multiscale or multilevel design problem in which it is important to map the input design space for an upper-level subproblem because it may define the performance constraints of a lower-level subproblem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation